Kinerja Dinas Ketenagakerjaan dalam Meningkatkan Kualitas Tenaga Kerja Di Kota Makassar - Dahyar Daraba; Alim Bachri Subianto (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2018)
There is still a large number of unemployment shows that the education and training that is given is still rated less, low skill labour-owned cause the quality of the workforce has become low. Therefore, this research aims to find out how the performance of the Employment Service in improving the quality of the workforce as well as the training provided and the efforts made.The research methods used is qualitative reasearch methods with descriptive approach. The informants in this research were the employees of the Department of Employment obtained by purposive sampling technique, and people who are getting who are getting employment administraton services. Data collection techniques carried out by direct interviews with structured techniques, observation and study document. Then the data analysis techniques used in this research is done by data reduction, display data and conclusion drawing. The results of this research show that the performance of the Employment Service in raising the quality of labor votes not optimal. It can be seen from the process of granting of services that already have a good information system, a good training methods, attitude of the staff who are friendly and courteous, responsive in dealing with the complaint of the community as well as the implementation of the activities of the socialization has been done effectively.